Research on agricultural development in five English-speaking countries in West Africa - Eicher, Carl K. (New York : Agricultural Development Council, 1970)
In this book, written by an agricultural economist, West Africa's rural development problems in the 1970's are considered, with special reference to Nigeria; past research is also briefly analysed and priorities given to research problems. An extensive bibliography, including references to West Africa as a whole and to The Gambia, Ghana, Liberia, Nigeria and Sierra Leone, occupies two thirds of the book.
Bibliography: p. 46-149.
lje 14/06/17
Loans
Keywords: Agriculture--Economic aspects; Agriculture--Economic aspects--Research; Agriculture; Africa, West; Africa, English-speaking